Math Problem Statement

In Exercises 1–6, find the average rate of change of the function over the given interval or intervals.

Solution

The exercise asks to calculate the average rate of change of given functions over specified intervals. The average rate of change of a function f(x)f(x) on an interval [a,b][a, b] is calculated using the formula:

Average Rate of Change=f(b)f(a)ba.\text{Average Rate of Change} = \frac{f(b) - f(a)}{b - a}.

Let's go through the first few exercises to illustrate the solution process:


1. f(x)=x3+1f(x) = x^3 + 1

(a) Interval [2,3][2, 3]

f(3)=33+1=27+1=28,f(2)=23+1=8+1=9f(3) = 3^3 + 1 = 27 + 1 = 28, \quad f(2) = 2^3 + 1 = 8 + 1 = 9 Average Rate of Change=f(3)f(2)32=2891=19\text{Average Rate of Change} = \frac{f(3) - f(2)}{3 - 2} = \frac{28 - 9}{1} = 19

(b) Interval [1,1][-1, 1]

f(1)=13+1=2,f(1)=(1)3+1=1+1=0f(1) = 1^3 + 1 = 2, \quad f(-1) = (-1)^3 + 1 = -1 + 1 = 0 Average Rate of Change=f(1)f(1)1(1)=202=1\text{Average Rate of Change} = \frac{f(1) - f(-1)}{1 - (-1)} = \frac{2 - 0}{2} = 1


2. g(x)=x22xg(x) = x^2 - 2x

(a) Interval [1,3][1, 3]

g(3)=322(3)=96=3,g(1)=122(1)=12=1g(3) = 3^2 - 2(3) = 9 - 6 = 3, \quad g(1) = 1^2 - 2(1) = 1 - 2 = -1 Average Rate of Change=g(3)g(1)31=3(1)2=42=2\text{Average Rate of Change} = \frac{g(3) - g(1)}{3 - 1} = \frac{3 - (-1)}{2} = \frac{4}{2} = 2

(b) Interval [2,4][-2, 4]

g(4)=422(4)=168=8,g(2)=(2)22(2)=4+4=8g(4) = 4^2 - 2(4) = 16 - 8 = 8, \quad g(-2) = (-2)^2 - 2(-2) = 4 + 4 = 8 Average Rate of Change=g(4)g(2)4(2)=886=0\text{Average Rate of Change} = \frac{g(4) - g(-2)}{4 - (-2)} = \frac{8 - 8}{6} = 0


Would you like me to continue solving the remaining problems or explain a specific part of these calculations in more detail? 😊

Here are 5 related questions to deepen your understanding:

  1. How is the formula for the average rate of change connected to the concept of a derivative?
  2. Why does the average rate of change become zero in Exercise 2(b)?
  3. Can you think of a real-world scenario that uses the concept of average rate of change?
  4. How can you graphically interpret the average rate of change on a function's graph?
  5. What happens to the average rate of change as the interval shrinks to a single point?

Tip: Always double-check your endpoints aa and bb to ensure correct substitution in the formula!

Ask a new question for Free

By Image

Drop file here or Click Here to upload

Math Problem Analysis

Mathematical Concepts

Algebra
Calculus
Average Rate of Change

Formulas

Average Rate of Change = (f(b) - f(a)) / (b - a)

Theorems

Slope of Secant Line

Suitable Grade Level

Grades 11-12